Pore Pressure Gradient Prediction for Deep Well/ Southern Iraq Oilfield (Sebha University Conference Proceedings, 2025)
Pore pressure prediction is crucial for drilling success and is a critical component of the 1D-MEM. It helps estimate in-situ horizontal stresses and predict the safe mud weight window for stable wellbore drilling. This study was conducted in deep well X, Field "H" in Southern Iraq, where wellbore instability causes high non-productive time and high costs of laboratory tests to measure pore pressure. Open-hole log measurements, including gamma ray log, density log, shear sonic log, compressional sonic log) to calculate vertical stress, shear stress, and formation water pressure. The Yamama Formation showed abnormal pore pressure Its value is 10285 psi compared to other formations whose value is less than 7581 psi. The Bowers original method was found to be more accurate than Eaton's method, as it failed to predict abnormal pore pressure based on the results of comparing both methods with laboratory results. Therefore, the study recommends using the Bowers original method for pore pressure calculations.